Monolithic active-quenching and active-reset circuit for single-photon avalanche detectors. - Zappa, F.
A monolithic circuit has been designed for active-quenching and active-reset of single-photon avalanche diodes (SPADs), which operate above the breakdown voltage VBD for detecting single photons. To the best of our knowledge, this is the first fully integrated circuit of this kind ever reported. It can operate with any available SPAD device, since it generates pulses high enough to quench detectors biased up to 20 V above VBD. The deadtime after each photon detection is adjustable; the minimum value is 50 ns, corresponding to 20 Mcounts/s maximum saturated photon-counting rate. The power dissipation is low (20-mW standby), suitable also for portable instruments. The small size and high reliability of the circuit make it possible to develop miniaturized detector modules and SPAD-array detector instruments. The circuit opens the path to new developments in many applications of photon counting, from DNA sequencing to ultrahigh-sensitivity imaging.
Keywords: SPAD array detector; Active-quenching.; Active-reset.; Monolithic integrated circuit; Photon counting; Portable instrument; Power dissipation; Single-photon avalanche detector